Механізми виникнення порушень морфо-функціонального стану сперматозоїдів та їх корекція у чоловіків репродуктивного віку в умовах великого промислового міста (Запоріжжя та Запорізька область) - Ломейко, Олена Олександрівна; Ломейко, Е. А.; Lomeiko, O. O. (Запорізький державний медичний університет, 2020)
У роботі проаналізовані особливості порушення морфології сперматозоїдів та гормонального статусу у чоловіків, що працюють в шкідливих виробничих умовах (із переважанням високих або низьких температур, стресорних навантажень, контактів із сільськогосподарськими добривами та отрутохімікатами), розроблено ефективний лікувальний комплекс, що включав антиоксидантно-метаболітну терапію при виявленому порушенні сперматогенезу та наявності одного з трьох негативних ознак (за ВООЗ, 2010р.) оліго-, астено- або тератозооспермії; гормональну терапію (при зниженому рівні тестостерону ˗ замісна терапія местеролоном, при гіперпролактинемії – прийом інгібітору секреції пролактину каберголіну); при наявності порушень тестикулярного кровообігу ˗ призначення венотоників та протинабрякової терапії. В результаті тримісячного лікування відбулося відновлення порушеної сперматогенної функції та гормонального балансу, підтверджено біологічне батьківство у чверті пацієнтів. В работе проанализированы особенности нарушения морфологии сперматозоидов и гормонального статуса у мужчин, работающих во вредных производственных условиях (с преобладанием высоких или низких температур, стрессорных нагрузок, контактов с сельскохозяйственными удобрениями и ядохимикатами), разработан эффективный лечебный комплекс, включавший антиоксидантно-метаболитную терапию при обнаруженном нарушении сперматогенеза и наличии одного из трех негативных признаков (по ВООЗ, 2010г.) олиго-, астено- или тератозооспермии; гормональную терапию (при пониженном уровне тестостерона ˗ заместительная терапия местеролон, при наличии нарушений тестикулярного кровообращения ˗ назначение венотоников и противоотечной терапии. В результате трехмесячного лечения произошло восстановление нарушенной сперматогенной функции и гормонального баланса, подтверждено биологическое отцовство у четверти пациентов. The peculiarities of sperm morphology and endocrine status disorders in men working in hazardous production conditions were analyzed, an effective treatment complex was developed, taking into account etiopathogenetic features of negative occupational influences (with predominance of high or low temperatures, stress loads and contact with pesticides) in male infertility. It is determined that the complete "triad" of spermiological changes (according to WHO criteria, 2010) oligo-, astheno- and teratozoospermia, are formed under conditions of prolonged exposure to high temperatures or contact with agricultural fertilizers and pesticides, while other negative occupational effects cause or bicomponent disorders: low temperatures form asthenozoospermia, prolonged stress - oligo- and asthenozoospermia revealed the etiodependence of changes in hormonal status in infertile men who work under the influence of adverse occupational factors. The correlation between the total number of sperm in the ejaculate (r = -0.67, p <0.05) and the percentage of sperm with translational and non-translational movement r = -0.67 (p <0.05) with a duration of occupational history was reliable only in a group of men working in high temperatures. The nature of changes in hormonal status in infertile men working under adverse occupational factors is etiologically dependent. With prolonged temperature exposure (low or high) hormone levels are within reference values and do not require appropriate correction, while stress during occupational activities leads to the formation of secondary hypogonadism due to disruption of the regulatory connection of the hypothalamic-pituitary-gonadal axis. In contrast, prolonged contact with agricultural fertilizers and pesticides forms primary hypogonadism, characterized by a decrease in total (2 times) and free (2 times) testosterone on the background of increasing concentrations of luteinizing hormone by 2.47 times and follicle-stimulating hormone by 60% with a decrease the testosterone / estradiol ratio is 2.35 times. The blood circulation in the main vessels of the testis in infertile men working under the influence of adverse external factors has an etiological dependence: in low temperatures there is a moderate decrease in almost all speed indicators; at high probable changes are noted only in the indicator of average minimum speed of blood circulation in a testicular artery of a seminal cord by 20% and a pulsation index; under conditions of stress in the testicular arteries at the level of the spermatic cord there is a significant and probable decrease in both the average maximum (by 35%) and average minimum (by 28%) circulatory velocities; in conditions of contact with agricultural fertilizers and pesticides, significant changes in blood flow velocities are not detected. Based on the results of the changes in infertile men, etiopathogenetic treatment was developed and performed. Antioxidant-metabolic and vascular-anti-edematous therapy was recommended for men who work for a long time in conditions of low or high temperatures. The result of three months of treatment was an increase in the total number of sperm, partial restoration of their motor activity, restoration of the percentage of morphologically normal sperm and reduction of abnormal forms. Treatment helped to increase the testosterone-estradiol ratio with complete normalization of testicular circulation. Prolonged stress led to infertility in men due to significant violations of sperm parameters with the presence of oligo- and asthenozoospermia, formed secondary hypogonadism and minor changes in testicular circulation. Their treatment complex included antioxidant-metabolic, hormonal (replaced by synthetic androgens in combination with a prolactin inhibitor - cabergoline) and vascular anti-edema. The treatment resulted in the restoration of quantitative and qualitative indicators of the spermogram, normalization of hormonal balance and testicular circulation. The treatment complex for infertile men, long-term contact with agricultural fertilizers and pesticides, consisted of the appointment of antioxidant-metabolic, hormonal (substituted by synthetic androgens) and anti-edema therapies. As a result of three months of treatment there was an increase in the total number of sperm, restoration of their motor activity, an increase in the percentage of normal morphology by 7 times and a decrease in abnormal forms by 24% against the background of normalizing hormonal balance. The use of the developed treatment complexes, taking into account the etio-pathogenetic features of the formed male infertility, is effective and contributes not only to the restoration of impaired spermatogenic function and hormonal balance, the main result of long-term treatment was biological parenthood in a quarter of patients after three months.
Механизмы возникновения нарушений морфо-функционального состояния сперматозоидов и их коррекция у мужчин репродуктивного возраста в условиях крупного промышленного города (Запорожье и Запорожская область)
Mechanisms of morpho-functional disorders of sperm and their correction in men of reproductive age in a large industrial city (Zaporozhye and Zaporozhye region)
Keywords: чоловіче безпліддя; спермограма; гормональний статус; тестикулярний кровообіг; шкідливі виробничі умови; антиоксидантно-метаболітна терапія; мужское бесплодие; спермограмма; гормональный статус; тестикулярное кровообращение; вредные производственные условия; антиоксидантно-метаболическая терапия; male infertility; spermogram; hormonal status; testicular circulation; harmful production conditions; antioxidant-metabolic therapy